Cancer-derived exosomal circTMEM56 enhances the efficacy of HCC radiotherapy through the miR-136-5p/STING axis - Li Yuan; Yue Wang; Junjie Cheng; Shilin Lin; Aying Ma; Kunchao Li; Yiming Zheng; Zhaochong Zeng; Aiwu Ke; Chao Gao; Shisuo Du (Cancer Biology & Medicine)
Objective: Although the role of circular RNAs (circRNAs) in tumor progression and immune regulation is well-known, the specific circRNA molecules that mediate immune responses after radiotherapy (RT) and the underlying mechanisms have not been identified. Methods: Cytometry with time-of-flight (CyTOF) was used to analyze blood samples from patients with liver cancer exhibiting abscopal effects (AEs) after stereotactic body radiotherapy (SBRT) to quantify the number of dendritic cells (DCs) and CD8+ T cells and interferon-beta (IFN-β) level. circTMEM56 and IFN-β levels were measured in 76 patients with liver cancer using qPCR and ELISA. Immunohistochemistry validated circTMEM56 and CD141 staining in tissues. The interaction between circTMEM56, miR-136-5p, and STING, as well as the impact on anti-tumor immunity, was verified using circTMEM56-specific probes, dual-luciferase activity assays, proteomics analysis, and western blot analysis. Results: The role of circTMEM56 in enhancing anti-tumor immunity and response to RT in hepatocellular carcinoma (HCC) was determined. Higher circTMEM56 levels were linked to an improved RT response and better clinical outcomes in patients with HCC. circTMEM56 enhanced cGAS-STING signaling, increased the number of tumor-infiltrating CD8+ T cells, and elevated the serum IFN-β levels. Moreover, circTMEM56 administration significantly boosted the response to RT in tumors with low circTMEM56 expression. Conclusions: High circTMEM56 expression in HCC modulates the distant effects of HCC RT by activating the cGAS-STING pathway to reshape the tumor microenvironment. This study provides a new approach to improve RT efficacy for HCC.